Pengaruh Kualitas Pelayanan Kartu Keluarga dan Kepercayaan Masyarakat Terhadap Kepuasan Masyarakat di Kecamatan Cimahi Tengah - Dewi, Tin Gantini; Saputra, Ginanjar Wira; Istikomah, Istikomah (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This studi focus to find out the effect of service quality and community satisfaction when making family cards in Cimahi Tengah District. A total of 49 people were the sample in this study, which used descriptive analysis. Multiple regression was used in analyzing data with SPSS 23. The results indicated that the X1 variable, namely service quality, and the X2 variable, namely trust, had a significant effect on the Y variable, namely community satisfaction in making family cards in Central Cimahi District. The coefficient of determination obtains a result of 78.5% which means that it shows that the two variables X which in this case are service quality and people’s trust have a strong relationship in increasing community satisfaction.